Kajian Peningkatan Mutu Sayuran pada CV. Sun Farm Kabupaten Cianjur - Gibza Adam Farhandika; Heti Mulyati; Nisa Zahra (Jurnal Manajemen dan Organisasi, 2019)
CV. Sun Farm is a vegetable distributor company in Cianjur, West Java. Nowadays the company faces the problems in the form of vegetable damage. The purpose of this study are to assess the implementation of vegetable quality management, to identify the causes of vegetable damage, and to recommend the strategies to improve the vegetables quality. The research method used Pareto Diagram to calculate the biggest losses that occur in vegetables, Fish Bone Diagram to determine the causes of vegetable quality problems and Analytical Hierarchy Process to formulate a strategy to improve the quality of vegetables, Implementation of quality management in companies is still simple, including leadership commitment to meet customer satisfaction. The vegetables that caused the highest losses were baby beans and horinso. Vegetable damage occurs due to human factors: the lack of rigorous employee work and employees who don't arrive on time. The strategy to maintain and improve the quality of vegetables is training for old employees and new employees.